Complexos de rutênio(III) com bases de Schiff tridentadas e tetradentadas do tipo Salophen : potenciais catalisadores na oxidação de catecol - Katayama, Juliana Midori Toia (Universidade Federal de São Carlos, 2015)
Ruthenium complexes are known as versatile electron-transfer and energy-transfer compounds. Due to these unique characteristics, ruthenium complexes exhibit a wide range of applications in various research areas such as artificial photosynthesis, photomolecular devices, biological probes, oxidation catalysts and organic synthesis. In the last two decades, salophen ligands and their complexes have received much attention, mainly because of their extensive applications in the fields of synthesis and catalysis. Thus, ruthenium(III) complexes with Schiff bases have several potential applications in the catalytic reactions such as cyclopropanation, epoxidation, aziridination, sulfimidation, catechols oxidation and Diels-Alder reactions. In this work were synthesized ligands and ruthenium complexes containing tridentate and tetradentate Schiff bases, which have substituted aromatic diimines, with satisfactory yields. The compounds synthesized in this work were characterized by melting point measurements, solubility tests, conductivity measurements, vibrational spectroscopy in the IR region, absorption spectra in the UV-vis, and cyclic voltammetry. The ligands were also characterized by nuclear magnetic resonance. The synthesized complex catalyzed oxidation of the substrate, 3,5-di-tert-butylcatechol, in their respective quinone; and these transformations were accompanied by absorption spectroscopy in the UV-vis region in 24 hours of reaction. The complexes’ structures have allowed structural and electronic effects to be evaluated and correlated with their catalytic activities. Although slow and low substrate conversion, less than 30%, trends were observed for correlations between structure and catalytic activity. The percentages of 3,5-di-tert-butilquinone obtained for the best catalysts among these complexes suggests that there is a step of forming a catalytically active species during the reaction time.
Ruthenium (III) complexes with tridentate and tetradentate salophen type Schiff bases : Potential catalysts in the oxidation of catechol.
Keywords: Química inorgânica; Complexos de rutênio; Schiff, Bases de; Oxidação de catecol; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA